Cadmium physiologically based pharmacokinetic (PBPK) models for forward and reverse dosimetry: Review, evaluation, and adaptation to the U.S. population. (15th August 2022) - Pouillot, Régis; Farakos, Sofia Santillana; Spungen, Judith; Schaefer, Heather R.; Flannery, Brenna M.; Van Doren, Jane M.
Abstract: The goal of this study was to assess a cadmium (Cd) physiologically based pharmacokinetic (PBPK) model to evaluate Cd toxicological reference values ( e.g. reference dose, tolerable intake, minimum risk level) adapted to the U.S. population. We reviewed and evaluated previously published Cd PBPK models and developed further adaptations to the 1978 Kjellström and Nordberg (KN) model. Specifically, we propose adaptations with updated U.S.-specific bodyweight, kidney weight and creatinine excretion models by using NHANES data as well as a stochastic PBPK model that provides credible intervals of uncertainty around mean populational estimates. We provide our model review and adaptations as well as present estimates from the newly adapted models using observed U.S. urinary Cd values as a function of gender and age and given dietary exposure as evaluated from NHANES/WWEIA and U.S. Total Diet Study data. Results show all newly adapted models provide acceptable mean estimates of urinary Cd in the U.S. The stochastic model provides credible intervals to further inform regulatory decision making. Validation of the estimated K-Cd concentration values was not possible as data for a representative population was not available. We developed a web-based tool implementing these models and other potential adaptations to facilitate PBPK model estimate comparisons. Highlights: We reviewed, and evaluated previously published Cd PBPK models for use in setting toxicological reference values. We developed U.S specific bodyweight, kidney weight and creatinine excretion models. We developed a stochastic PBPK model that properly estimates exposure by reverse dosimetry. We developed a tool to facilitate model estimate comparisons using forward and reverse dosimetry.